VIDEO MPEG-1 - Candra, Henry (Jurnal Teknik Elektro, 2002)
MPEG-1 is one of the standards to encode the information in digital signal. This standard iswidely used in many application such audio, video and teleconferencing. The concept of theMPEG-1 video encoding is discussed in this paper to give better understanding to the readerof what MPEG-1 Video, and how it can be more applicable. The benefits of MPEG-1 videoencoding are the file size produced is smaller than the source, the standard has been used inmany applications, and also the encoding and decoding process are easy to do back andforth.Keywords: MPEG-1, audio/video, teleconferencing, encoding, decoding